Predictors of liver cirrhosis and hepatocellular carcinoma among perioperative survivors of the Fontan operation. Issue 4 (29th June 2022) - Inuzuka, Ryo; Nii, Masaki; Inai, Kei; Shimada, Eriko; Shinohara, Tokuko; Kogiso, Tomomi; Ono, Hiroshi; Otsuki, Shin-ichi; Kurita, Yoshihiko; Takeda, Atsuhito; Hirono, Keiichi; Takei, Kota; et al.
Abstract : Objective: Fontan-associated liver disease (FALD) is widely recognised as a common complication in patients long after the Fontan operation. However, data on the predictors of FALD that can guide its screening and management are lacking. The present study aimed to identify the predictors of liver cirrhosis (LC) and hepatocellular carcinoma (HCC) in post-Fontan patients. Methods: This was a multi-institutional retrospective cohort study. Clinical data of all perioperative survivors of Fontan operation before 2011 who underwent postoperative catheterisation were collected through a retrospective chart review. Results: A total of 1117 patients (538 women, 48.2%) underwent their first Fontan operation at a median age of 3.4 years. Postoperative cardiac catheterisation was conducted at a median of 1.0 year. During a median follow-up period of 10.3 years, 67 patients (6.0%) died; 181 (16.2%) were diagnosed with liver fibrosis, 67 (6.0%) with LC, 54 (4.8%) with focal nodular hyperplasia and 7 (0.6%) with HCC. On multivariable analysis, high central venous pressure (CVP) (HR, 1.28 (95% CI 1.01 to 1.63) per 3 mm Hg; p=0.042) and severe atrioventricular valve regurgitation (HR, 6.02 (95% CI 1.53 to 23.77); p=0.010) at the postoperative catheterisation were identified as independent predictors of LC/HCC. Conclusions: Patients with high CVP and/or severe atrioventricular valve regurgitation approximately 1 year after the Fontan operation are at increased risk of developing advanced liver disease in the long term. Whether therapeutic interventions to reduce CVP and atrioventricular valve regurgitation decrease the incidence of advanced liver disease requires further elucidation.